Pharmacomicrobiomics of cell-cycle specific anti-cancer drugs – is it a new perspective for personalized treatment of cancer patients? - Karolina Kaźmierczak-Siedlecka; Nikola Bulman; Paweł Ulasiński; Bartosz Kamil Sobocki; Karol Połom; Luigi Marano; Leszek Kalinowski; Karolina Skonieczna-Żydecka (Gut Microbes, 2023)
ABSTRACTIntestinal bacteria are equipped with an enzyme apparatus that is involved in the active biotransformation of xenobiotics, including drugs. Pharmacomicrobiomics, a new area of pharmacology, analyses interactions between bacteria and xenobiotics. However, there is another side to the coin. Pharmacotherapeutic agents can significantly modify the microbiota, which consequently affects their efficacy. In this review, we comprehensively gathered scientific evidence on the interplay between anticancer therapies and gut microbes. We also underlined how such interactions might impact the host response to a given therapy. We discuss the possibility of modulating the gut microbiota to increase the effectiveness/decrease the incidence of adverse events during tumor therapy. The anticipation of the future brings new evidence that gut microbiota is a target of interest to increase the efficacy of therapy.